Integrasi Teknologi IoT dan Aplikasi Telegram Untuk Pemantauan Kadar Gula Darah Penderita Diabetes: Membuat sebuah alat pengecekaan kadar gula darah secara non-invasive - Jessa Syah Putra; Deny Nugroho Triwibowo; Rian Ardianto (ITB Ahmad Dahlan Jakarta, 2025)
Blood sugar (glucose) is the body's main source of energy and is classified as a monosaccharide. Blood sugar levels are divided into low, normal, and high, with high levels potentially triggering diabetes, one of the main health issues in Indonesia. This research proposes an Internet of Things (IoT)-based health monitoring system to measure blood sugar levels using a photodiode sensor and a red LED as the light source. The system is equipped with real-time notifications via Telegram and data display on an OLED screen. The method used is a prototype with accuracy testing against a glucometer as a comparison tool. The test results showed an average error of 5.28% out of a total error of 105.77%. However, the device often displays the same measurement results repeatedly and shows a “finger not detected” notification due to the sensor's sensitivity to surrounding light.